NATURAL-SCIENCE EDUCATION: SCIENTIFIC AND RELIGIOUS KNOWLEDGE CORRELATION IN THE VIEW OF A SYMMETRY PRINCIPLE. Ch. 2. Examples of religious content selection in general natural science courses based on the principle of symmetry - Vitalii L. Gapontsev; Marina G. Gapontseva (Russian State Vocational Pedagogical University, 2015)
This work is aimed at demonstrating the possibility of the inclusion of religious elements contained in Holy Scripture and Holy Tradition in the general natural scientific courses based on the principle of symmetry.The method used in the work is confined to a comparison of perceptions formed in modern science and is closely related to the forms of symmetry and invariance principles (symmetry principles) and, in particular, space-time concepts with those of the Book of Genesis. Such a comparison reveals the following unexpected feature: most profound presentation of modern natural sciences is closer to the provisions of Holy Scripture and Holy Tradition than a look at the same things existed in the earlier stages of the development of science. This allows the authors to formulate the hypothesis that in the process of development of scientific knowledge, it gradually becomes closer to the religious worldview. This process is slow, so its results have become visible only within 3500 years after the establishment of the truth of the Old Testament and 2000 years after the New Testament.Results and scientific novelty. The «firmament of heaven» and «water under the firmament» concepts are explained in the terms of the model of the Kleinert - Planck World crystal and understanding of the properties of matter and fields which are related with the conservation law of the wave-function parity. The relational nature of phenomena such as «life» and «death» in the course of universe evolution as a general trend is considered as the process of lowering the degree of symmetry of matter after the Big Bang wherein the Universe was created. The concepts used by E. Wigner for the description of the structure of the scientific knowledge are analysed. Its structure is determined by shapes and specific principles of the symmetry of exact sciences. The analysis of the concept «natural phenomenon» has shown that they are different in the degree of space-time localization. As the nonlocality of nature phenomenon becomes intensive, the limits of the scientific knowledge are approached. Understanding of creatures with the utmost degree of nonlocality is beyond the scientific knowledge. There is a tendency in modern science to study the behavior of objects in frames of nonlocal spacetime description. This trend is reflected, for example, in a study of the phenomenon of quantum entanglement. It can be stated that in this respect the position of science closes in the positions of the religious worldview.Practical significance. In this paper the authors present a few examples of selection of content of the course based on the Principle of symmetry.